Repetition of the Marriage Contract (Shihhah) in the Rifaiyah’s Tradition - Muftadin, Dahrul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
In the tradition of Jama'ah Rifaiyah there is the practice of repeating the marriage contract called Shihhah. This tradition emerged from the understanding of the central figure of the Rifaiyah congregation, Kiai Ahmad Rifai, who categorized some Muslims who supported the Dutch colonial government into the category of wicked believers, including the Penghulu (Chieftain). Penghulu who are under the auspices of the colonial government are considered no longer have a